2004
DOI: 10.1021/bp049976w
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A newly developed shearing device was used to study shear-induced inactivation of thermostable alpha-amylase in a plain shear field, under conditions comparable to extrusion. The results show that the inactivation can be described well with a first-order process, in which the inactivation energy largely depends on the shear stress, instead of specific mechanical energy or strain history. The resulting dependency of the rate of inactivation on the shear stress is very strong and nonlinear, which leads to the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Jyothi et al reported that Fe­(II) increased PV of cassava starch treated in the absence of α-amylase, and similar results were obtained with Cu­(II). The influence of enzyme-Fe/Cu combination on pasting viscosity should be further studied to find more evidence that could explain the decrease of the enzyme activity in the presence of these cations . However, especially considering the shearing and pressure effects occurring during the extrusion process, some evidence and possible inactivation mechanisms are given below.…”
Section: Resultsmentioning
confidence: 81%
“…Jyothi et al reported that Fe­(II) increased PV of cassava starch treated in the absence of α-amylase, and similar results were obtained with Cu­(II). The influence of enzyme-Fe/Cu combination on pasting viscosity should be further studied to find more evidence that could explain the decrease of the enzyme activity in the presence of these cations . However, especially considering the shearing and pressure effects occurring during the extrusion process, some evidence and possible inactivation mechanisms are given below.…”
Section: Resultsmentioning
confidence: 81%
“…Dividing cells are probably more shear sensitive. Step responses to shear stress have previously been reported for enzymes [36] and starch molecules [37, 38], suggesting a more general role of shear stress in deactivation and breakage processes.…”
Section: Resultsmentioning
confidence: 92%
“…Another possible way to increase the shear-induced forces is to use a solvent with a larger viscosity than water, as is the case in the study by van der Veen et al [35] on α-amylase deactivation in concentrated starch solution. Due to the very high viscosity of the medium, relatively large shear stresses of about 3×10 4 Pa were reached, which have partially deactivated the enzyme by deforming its tertiary structure.…”
Section: Proteins In the Flow: Experimental Resultsmentioning
confidence: 99%